Recent advances in flow injection analysis. Issue 7 (24th February 2016) - Trojanowicz, Marek; Kołacińska, Kamila
Abstract : A dynamic development of methodologies of analytical flow injection measurements during four decades since their invention has reinforced the solid position of flow analysis in the arsenal of techniques and instrumentation of contemporary chemical analysis. Abstract : A dynamic development of methodologies of analytical flow injection measurements during four decades since their invention has reinforced the solid position of flow analysis in the arsenal of techniques and instrumentation of contemporary chemical analysis. With the number of published scientific papers exceeding 20 000, and advanced instrumentation available for environmental, food, and pharmaceutical analysis, flow analysis is well established as an extremely vital field of modern flow chemistry, which is developed simultaneously with methods of chemical synthesis carried out under flow conditions. This review work is based on almost 300 original papers published mostly in the last decade, with special emphasis put on presenting novel achievements from the most recent 2–3 years in order to indicate current development trends of this methodology. Besides the evolution of the design of whole measuring systems, and including especially new applications of various detections methods, several aspects of implications of progress in nanotechnology, and miniaturization of measuring systems for application in different field of modern chemical analysis are also discussed.